El juego y las habilidades sociales en la enseñanza semipresencial en niños de la Institución Educativa Inicial N° 160 Mi Primer Aprendizaje, Caballococha 2022 - Tapayuri Bardales, Asucena (2023)
Games and social skills are two important aspects of the development of children in the school environment, which is why this study had as its main objective to relate games and social skills in blended learning in children of the Initial Educational Institution N °160 My First Learning of Caballococha. Therefore, the design and type of research were field, bivariate, cross-sectional, and relational, respectively. 59 school children were part of the population and sample, in which data was collected through the observation technique and observation guides, instruments that went through the expert test to obtain their validity. The research concludes by stating that there is a relationship between play and social skills in the 59 (100.0%) children of the I.E.I. N° 160 "My first apprenticeship" of Caballococha because the correlation coefficient of rxy= 0.637, a value that shows the existence of a strong, direct and positive relationship between both variables, which means that as the games increase, the social skills in children improve and are increasing.